PROFITABILITY OF RICE PRODUCTION IN FUFORE LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NIGERIA - Girei, A. A.; Onuk, E. G. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The study analysed the profitability analysis of rice production in Fufore local government area of Adamawa state, Nigeria. Primary data which were obtained through the use of scheduled interview using structured questionnaire was used for the study. Frequency, percentages and budgetary technique were used to analyse the data. The results showed that 65% of the respondents had no formal education and financed their rice production through personal savings. About 82% of the respondents had more than 10 years’ experience in rice farming, 70% have household size of more than 5 people and 91% of the respondents had no extension visits. Equally worth mentioning from the result is that an average total cost of N270,864 was incurred per annum by the rice farmers while gross revenue of N740,000 was realized with gross margin of N494.940 and a profit of N469,136 and returned to Naira on investment of N0.37 were recorded. The study concluded that rice production in the study area is economically rewarding, profitable and sustainable with high propensity to achieving self-sufficiency in food security and poverty reduction. The study recommends adequate more extension visits to the respondents. The resource structure also revealed that majority of the farmers practiced small scale farming and had little access to financial support. In this regards, government and relevant stakeholders should actively participate in rice production in order to improve and boost the quantity and quality of rice availability for domestic consumption and export. Rice farming in the study area is dominated by male farmers. Female gender need to be motivated and encouraged to participate as a possible means of complementing their income that will ensure sustained livelihood. The farmers should be organized into cooperative and where it exist, they should be strengthen and become a formidable force to be reckoned with especially in decision and policy making on issues affecting their interest.